Symptoms of anxiety and depression among Slovenian breast cancer survivors post treatment during the COVID-19 pandemic - Miroševič, Špela (Zdravstveno varstvo, 2024)
Background: Although anxiety and depression are important determinants of mental health, the literature in this area is sparse as most studies focus on the period during treatment. Mental health problems can affect cancer recovery as well as quality of life and survival. In this cross-sectional study, we investigated the prevalence of anxiety and depression in Slovenian cancer survivors after treatment and assessed the associated correlates during the COVID-19 pandemic. Methods: From September 2021 to January 2022, we collected data from 430 breast cancer survivors one to five years after receiving post-local treatment and (neo)adjuvant chemotherapy. We used the Hospital Anxiety and Depression Scale (HADS) to measure anxiety and depression levels. Multivariate linear regression was used to identify factors associated with higher levels of anxiety and depression. Results: Key findings from this study are increased levels of psychological distress and identification of relevant factors associated with those elevated levels. Approximately one-third of breast cancer survivors exhibited symptoms of elevated anxiety and depression, with one in eight meeting clinical thresholds. Multivariate linear regression revealed that age, lower quality of life, heightened fear of cancer recurrence (FCR), reduced resilience, limited social support, and unmet psychosocial and emotional needs correlated with increased anxiety symptoms. Additionally, lower quality of life, higher FCR, diminished resilience, and limited social support were associated with higher depression symptomatology. Conclusions: Our study of Slovenian breast cancer survivors one to five years post-treatment observed a significant increase in anxiety and depression symptoms, possibly exacerbated by the COVID-19 pandemic. The demographic and psychosocial factors identified in this study offer valuable insights for future research. The study emphasises the importance of recognising and addressing the psychological needs of breast cancer survivors and the need to follow them throughout their cancer journey.
Keywords: anksioznost; anxiety; breast neoplasms; covid -19; COVID-19; depresija; depression; psihološki distres; psychological distress; rak dojke